PERANCANGAN ANIMASI 2D EDUKASI MENGENAI VIRUS OMICRON DESAIN KOMUNIKASI VISUAL - Adji Wicaksono, Reuben (Universitas Budi Luhur, 2023)
Currently, there are still many people who still lack knowledge about the omicron virus in terms of how it works and how to prevent it so that it can be detrimental to many people who still lack knowledge of the omicron virus. With that, I will create a 2d animation that is educational in nature about the omicron virus. With the existence of social media, in terms of learning or educating many people, it is possible to make education more effective and efficient. Based on the results of the data that has been collected, this asks about what we already know about Omicron from the way it works, the appearance of Omicron from a variant of the Corona virus that has mutated into the newest virus and can also stop all protection from the vaccine that we make. Based on the results of the data that has been collected, this asks about what we already know about Omicron from the way it works, the appearance of Omicron from a variant of the Corona virus that has mutated into the newest virus and can also stop all protection from the vaccine that we make.